THU0108 Closing The Audit Cycle: Have Cardiovascular Risk Assessment and Management in Rheumatoid Arthritis Patients Improved?. (15th July 2016) - Magro, R.; Bartolo, K.; Corso, R.; Buhagiar, M.; Taliana, N.; Borg, A.
Abstract : Background: Patients who suffer from rheumatoid arthritis have an increased risk of morbidity and mortality from cardiovascular disease. This is due to the high prevalence of traditional risk factors and the effect of systemic inflammation. Objectives: The aim of the audit was to determine whether the cardiovascular risk assessment and management in rheumatoid arthritis patients at Mater Dei Hospital is in concordance with the recommendations by the European League Against Rheumatism (EULAR). Methods: An audit was carried out retrospectively on 91 patients who suffer from rheumatoid arthritis by using the medical notes to collect data on demographics, co-morbidities, drug history and cardiovascular risk assessment and management over a two year period (August 2010 to July 2012). The results of the first audit were then disseminated through the rheumatology department and a form for cardiovascular risk assessment and management in rheumatoid arthritis patients was implemented. The audit was repeated on 107 patients and data was collected retrospectively over the two year period starting from January 2013 to December 2014. Results: Documentation of cardiovascular risk factors over the two year period audited improved as follows from the first to the second audit: weight in 27.5% to 52.3%, height in 0% to 27.1%, BMI in 0% to 10.3%, smoking status in 72.5% to 93.5%, blood pressure in 72.5% to 92.5%, blood glucose in 72.5% to 97.1% and lipid profile in 54.9% to 96.3%. Documentation of smoking cessation advice improved from 15.8% to 41.1% and advice on other lifestyle changes improved from 14.3% to 18.7%. Moreover calculation of DAS28 over a one year period improved from 20.9% to 51.4%. In the first audit, 13.8% of patients who had complete data and in whom the ten year cardiovascular risk could be calculated (29 patients), would benefit from the use of a statin according to the guidelines (and were not currently receiving one). In the re-audit, this decreased to 8.6% of such patients (93 patients). In the second audit it was noted that the form that had been introduced for cardiovascular risk assessment was used in 15% (16 patients). The documentation of lifestyle advice was significantly higher ( p <0.001) in the group of patients in whom the form was used. The same applies for documentation of weight ( p <0.001), height ( p <0.001), BMI ( p <0.001) and calculation of DAS28 over a one year period ( p <0.001). The prevalence of diagnosed hypertension in our cohort of rheumatoid arthritis patients was 49.0%; diabetes was 19.7%; hyperlipidaemia was 21.8%; and ischaemic heart disease was 8.8%. Conclusions: Cardiovascular risk factors are highly prevalent in rheumatoid arthritis patients. This audit showed that cardiovascular risk assessment and management improved through raising awareness of its importance in the rheumatology department as well as the implementation of the cardiovascular risk assessment form. References: Peters M JL, Symmons D PM, McCarey D, Dijkmans B AC, Nicola P, Kvien T K et al. EULAR evidence-based recommendations for cardiovascular risk management in patients with rheumatoid arthritis and other forms of inflammatory arthritis. Ann Rheum Dis, Feb 2010; 69: 325–33. Disclosure of Interest: None declared